2007
DOI: 10.1021/cm071165a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous α-Fe2O3 Nanorods and Deposition of Very Small Gold Particles in the Pores for Catalytic Oxidation of CO

Abstract: FeO(OH) nanorods were prepared by a mild hydrothermal synthesis using tetraethylammonium hydroxide (TEAOH) as the structure director. The as-prepared FeO(OH) was converted to porous α-Fe2O3 nanorods via calcination at 300 °C. The α-Fe2O3 nanorods have a pore size distribution in the range of 1−5 nm, which is ideal to house very small gold (Au) particles. Later, by employing our invented Au- colloid-method, in which lysine was used as the capping reagent and sonication was employed to facilitate the deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 50 publications
8
135
0
2
Order By: Relevance
“…We also made an effort to study the physicochemical properties of the catalysts and correlate the properties with catalytic CO oxidation activity. [21]. Typically, 1.0 g of Fe(NO 3 ) 3 ⋅9H 2 O was added to 10 mL of 0.1 N aqueous NH 4 H 2 PO 4 solution.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also made an effort to study the physicochemical properties of the catalysts and correlate the properties with catalytic CO oxidation activity. [21]. Typically, 1.0 g of Fe(NO 3 ) 3 ⋅9H 2 O was added to 10 mL of 0.1 N aqueous NH 4 H 2 PO 4 solution.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…A specific rate for CO oxidation for calcined 0.5Au-Fe catalyst was calculated and compared with reaction [21]. The enhanced activity of the catalyst could be attributed to the small size of the synthesized Au nanoparticles [48] and also the synthesized nanosized mesoporous Fe 2 O 3 support possessed a high surface area.…”
Section: Catalytic Oxidation Of Carbonmentioning
confidence: 99%
“…Zhong et al [41] also used porous Fe 2 O 3 as support but prepared Au catalysts in which small Au particles were inserted inside the pores. Fe(NO 3 ) 3 ·9H 2 O and tetraethylammonium hydroxide (TEAOH) were adopted as metal precursor and precipitant/structure directing agent, respectively.…”
Section: Goldmentioning
confidence: 99%
“…(2) can we find active gold catalysts based on previously overlooked supports (e.g., metal phosphates)? In addition, the effects of the crystal phase [65,82,[96][97][98][99][100], size [99,[101][102][103][104][105][106][107][108], and shape [45,[108][109][110][111][112][113][114] of solid supports on the catalytic performance are also of interest. Below we first present the development of Au/SiO 2 and Au/metal phosphate catalysts in our group, and then highlight recent findings on the effects of the particle size and shape of solid supports.…”
Section: General Considerationsmentioning
confidence: 99%
“…The authors proposed, based on diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) data, that the OH groups bonding to γ-Al 2 O 3 nanofibers may facilitate CO oxidation. Zhong and co-workers dispersed gold colloids onto porous α-Fe 2 O 3 nanorods, and found that the resulting catalyst was more active than gold nanoparticles dispersed on commercial α-Fe 2 O 3 [45]. Cao and coworkers found that the activity of Au/β-MnO 2 nanorods was higher than that of Au/commercial β-MnO 2 particulates in the solvent-free aerobic oxidation of alcohol [111].…”
Section: Effect Of the Particle Morphology Of The Supportmentioning
confidence: 99%